1995
DOI: 10.1159/000262092
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Evaluation of Occlusal Caries: Effect of Training and Experience

Abstract: The purpose of this study was to investigate what effect differing levels of didactic education and clinical experience have on the ability to diagnose occlusal caries from radiographs. Freshman and senior dental students and dental school faculty were asked to evaluate bitewing radiographs for the presence of occlusal caries and for a recommendation for restorative treatment. The agreement between histologic and radiographic diagnosis was assessed by calculating sensitivity, specificity, accuracy, and interex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 10 publications
4
25
0
1
Order By: Relevance
“…A separate value for any one of these parameters does not supply signifi cant information on the method of diagnosis in question [Thylstrup and Fejerskov, 1994]. Later studies [Noar and Smith, 1990;Nuttall and Pitts, 1990;Lazarchik et al, 1995] found that the more experienced the professional, the greater the ability to detect absence of lesion (specifi city); as a result, the choice for a restorative treatment was more careful. A possible explanation may be that the increasing knowledge of the etiology, initiation, progression and prevention of caries disease [Dodds, 1993;Basting and Serra, 1999] and the repetitive restorative cycle [Elderton, 1983] prompted a change of attitude with respect to the diagnosis of early caries lesions that resulted in more conservative treatment options.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A separate value for any one of these parameters does not supply signifi cant information on the method of diagnosis in question [Thylstrup and Fejerskov, 1994]. Later studies [Noar and Smith, 1990;Nuttall and Pitts, 1990;Lazarchik et al, 1995] found that the more experienced the professional, the greater the ability to detect absence of lesion (specifi city); as a result, the choice for a restorative treatment was more careful. A possible explanation may be that the increasing knowledge of the etiology, initiation, progression and prevention of caries disease [Dodds, 1993;Basting and Serra, 1999] and the repetitive restorative cycle [Elderton, 1983] prompted a change of attitude with respect to the diagnosis of early caries lesions that resulted in more conservative treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…populations with decreased caries prevalence, the proportion of occlusal caries has increased and the diffi culty of accurately detecting incipient pit-and-fi ssure lesions has been continuously discussed, reinforcing the interest for studying this type of carious lesion [Creanor et al, 1990;Dodds, 1993;Lazarchik et al, 1995;Lavaonius et al, 1997].…”
mentioning
confidence: 99%
“…The results obtained could be in part explained by Bader and Shugars's explanations, and partly by other factors such as age, training, skills, preferences and experiences of students and professionals, as described in Lazarchik et al 24 . In this regard, Héllen-Halme and Petersson 25 evaluated how variations in educational level and experience inf luenced diagnostic accuracy for the detection of approximal carious lesions.…”
Section: First Assesmentmentioning
confidence: 66%
“…Other studies have evaluated whether education level and experience can affect diagnostic accuracy of caries lesions in radiographs (Lazarchik et al, 1995;Mileman & van den Hout, 2002;Hellen-Halme & Petersson). Hellen-Halme & Petersson reported that experienced dentists diagnosed radiographic proximal caries more accurately than dental hygiene students and dentistry students.…”
Section: Discussionmentioning
confidence: 99%